2008
DOI: 10.1200/jco.2007.15.5945
|View full text |Cite
|
Sign up to set email alerts
|

Liver Cancer Stem Cells

Abstract: In an effort to review the evidence that liver cancer stem cells exist, two fundamental questions must be addressed. First, do hepatocellular carcinomas (HCC) arise from liver stem cells? Second, do HCCs contain cells that possess properties of cancer stem cells? For many years the finding of preneoplastic nodules in the liver during experimental induction of HCCs by chemicals was interpreted to support the hypothesis that HCC arose by dedifferentiation of mature liver cells. More recently, recognition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
162
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(166 citation statements)
references
References 72 publications
4
162
0
Order By: Relevance
“…First, an abundant oval cell response is likely to contribute to enhanced liver tumor formation in mice with attenuated hippo signaling activity. Oval cells are bipotental hepatic progenitor cells that are induced following carcinogen exposure in experimental models of hepatocellular carcinoma and are thought to function as cancer stem cells in these models (28,29). That we observe tumors of both biliary and hepatocyte lineages in sav1 mutant mice is consistent with an important contribution of oval cell activation in tumor formation.…”
Section: Transcripts Affected By Reduced Hippo Signaling In Hepatocytsupporting
confidence: 68%
“…First, an abundant oval cell response is likely to contribute to enhanced liver tumor formation in mice with attenuated hippo signaling activity. Oval cells are bipotental hepatic progenitor cells that are induced following carcinogen exposure in experimental models of hepatocellular carcinoma and are thought to function as cancer stem cells in these models (28,29). That we observe tumors of both biliary and hepatocyte lineages in sav1 mutant mice is consistent with an important contribution of oval cell activation in tumor formation.…”
Section: Transcripts Affected By Reduced Hippo Signaling In Hepatocytsupporting
confidence: 68%
“…The liver is a good objective for studying tissue stem cell differentiation into tumor tissue cells in vitro [55], since several stem cells lines can differentiate and regenerate into functional liver cells [59] , and effective hepatic differentiation protocols have already been established [49][50][51][52][53]60]. It has also been demonstrated that the in vitro produced hepatocyte-like cells transplanted into patients can differentiate into functional liver cells [6].…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell lines can be differentiated to hepatocyte-like cells implementing an in vitro model for the cancer cell formation from tissue stem cells [55]. During the differentiation process the continuous changes in the expression level of various genes can also be monitored [18,23,[56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…HepG2 was Cytotechnology (2015) 67:1-12 7 isolated from liver biopsy specimens of primary HB, whereas Hep3B was from primary HCC (Aden et al 1979;Knowles et al 1980). According to a hierarchical hepatic cellular lineage model for liver cell maturation and liver cancer development, HB is derived from neonatal liver stem cells with more potential and HCC is arisen from more differentiated mature hepatocytes in liver lobule (Sell and Leffert 2008). Hence, HepG2 and Hep3B come from different differentiation stages in liver cell lineage, which may well explain the differences between them.…”
Section: Underlying Mechanisms Responsible For the Differences Betweementioning
confidence: 99%